(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Pulmonary cryptococcosis (PC) describes an invasive lung mycosis caused by Cryptococcus neoformans or Cryptococcus gattii complex. PC is a very rare form of pneumonia, which is seldom seen among immunocompetent patients, and may be misdiagnosed as pulmonary tuberculosis, leading to a delay in therapy. Objective: This article aims to report in detail a case of PC in a healthy person, diagnosed based on CT-guided lung biopsy and histopathology. Cases contribute to scientific data, and share experiences about the diagnostic and treatment process. Case report: A 53-year-old female healthy subject was admitted to Hightech on-demand treatment center of National Lung Hospital because of cough and shortness of breath for 20 days. This patient had the complaints of irritating productive cough, chest tightness and a broad-spectrum antibiotic treatment was ineffective. Although the AFB sputum test was positive, a CT-guided lung biopsy was performed to and PC was diagnosed. Patient was treated by intravenous fluconazole for two weeks. The patient’s follow-up was performed, and we have seen the patient recovered and doing well. Discussion: Discuss clinical imaging features, differential diagnosis with pulmonary tuberculosis, and the role of biopsy and histopathology. Emphasize the importance of accurate diagnosis and monitoring of treatment response Conclusion: Summarizing the insights from the case report and discussion, the conclusion emphasizes the importance of accurate diagnosis and effective treatment strategies for PC. Further research and long-term follow-up are encouraged to gain a deeper understanding of this uncommon condition.